Things I Couldn't Tell My Mother : A Memoir - Johnston, Sue, 1943- (London Ebury Press, 2011)
"Sue Johnston always seemed to be disappointing her mother. As a girl she never stayed clean and tidy like her cousins. As she grew older, she spent all her piano lesson money on drinks for her mates down the pub, and when she discovered the Cavern she was never at home. The final straw was when Sue left her steady job at a St Helens factory to try her hand at that unsteadiest of jobs: acting. Yet when Sue was bringing up her own child alone, her mother was always there to help. And playing her much-loved characters Sheila Grant and Barbara Royle - although her mum wouldn't say she was proud as such, she certainly seemed to approve. And in her mother's final months, it was Sue she needed by her side. The relationship with your mother is perhaps the most precious and fraught of any woman's life. When she began writing, Sue set out to record 'all the big things, and all the small things. Everything I wanted to tell my mother but felt I never could'. The result is a warm, poignant and often very funny memoir by one of Britain's favourite actresses."--Back cover.
Include Illustration
Keywords: Great Britain -- Actresses -- Television actors and actresses -- Great Britain -- Biography